ELEMEN SPM TERHADAP KUALITAS INTERNAL PRODUK PADA PERUSAHAAN MANUFAKTUR BERSERTIFIKASI IS0 9001 DI SURABAYA, GRESIK, DAN SIDOARJO - Dara Enggal Herlawanti; Rovila El Maghviroh (The Indonesian Accounting Review, 2012)
TQM has been implemented in any organization. Through such a management, it is expected that any company and their employees can get their competitive advantage. This study investigates the influence of SPM on internal quality of the product. Continuing research by Maghviroh (2010), the researchers investigate the influence of management control system elements (Level Communication Quality Objectives, Quality Feedback Frequency and Effectiveness of Quality Incentive) on internal quality of the product. This study used the sample of manufacturing businesses whose ISO 9001 certification in Surabaya, Gresik and Sidoarjo. It is an empirical test, with the technique of random sampling, obtained from 11 manufacturing business (42 respondents) with ISO 9001 certification in Surabaya, Gresik and Sidoarjo. SPSS 17.0 for Windows was employed for data analysis. It showed that all hypotheses were accepted. There was a positive influence of the level of communication quality goals on internal quality product, second, positive influence of the feedback frequency on internal quality product quality, and also a positive influence of the effectiveness ofincentives on the quality of the internal quality of the product..